EVALUATION OF THE EFFECTIVENESS OF NATIONAL EDUCATION POLICIES IN ACHIEVING QUALITY LEARNING IN HIGHER EDUCATION IN INDONESIA - Halimatussa'diyah (International Journal of Teaching and Learning, 2023)
This study evaluates the effectiveness of national education policies in achieving quality learning in higher Education in Indonesia. Using a mixed-methods approach, quantitative and qualitative data were collected from diverse stakeholders, including university administrators, faculty members, and students. The analysis revealed that 75% of administrators actively aligned their curricula with national objectives, demonstrating a commendable commitment. However, a significant challenge emerged, with 60% of administrators highlighting difficulties securing adequate funding for policy implementation, indicating a substantial barrier to effective execution. Positive correlations were identified, such as an 80% satisfaction rate among students regarding the relevance of their coursework to national development goals. Faculty members, in turn, perceived a positive impact on teaching methodologies (65%). Statistical analyses affirmed these trends, indicating a significant association (p < 0.05) between faculty development programs funded through national policies and enhanced teaching effectiveness. Despite these positive findings, challenges in resource allocation and potential limitations in generalization were acknowledged. Recommendations include targeted interventions to address funding disparities and further research exploring longitudinal impacts and contextual nuances. This study contributes valuable insights to policymakers, educators, and researchers, offering a nuanced understanding of the complex dynamics influencing the quality of learning in Indonesia's higher education landscape.